ANALYSIS OF THE SPREAD OF THE KUJUNG CARBONATE RESERVOIR AND ITS IMPLICATIONS FOR HYDROCARBON VOLUMETRIC CALAVATIONS IN THE MIM FIELD, NORTHEAST JAVA BASIN - Irfan Mashudi, M.
The MIM field is one of the offshore fields owned by PT Pertamina EP Cepu which is located in the eastern part of the Java Sea Basin. This field was discovered in 2002. The main reservoir in the MIM field is the Kujung Formation with an average thickness of 600 feet. To find out the potential of this reservoir, it is necessary to analyze the distribution of the reservoir and determine the amount of gaseous hydrocarbon reserves in the reservoir or what is usually called Original Gas in Place (OGIP). This study aims to solve the problem of cumulative production numbers that have exceeded the amount of reserves in place (inplace) in the Kujung Formation so that a more comprehensive analysis is needed through the interpretation method of seismic geobody modeling and static models as well as making a three-dimensional model of the Kujung Formation and analyzing its influence on calculations volumetric hydrocarbon gas namely OGIP. The results of the reservoir distribution analysis show that the Kujung reservoir is identified as being divided into two main reservoir layers, namely Kujung Reef (reef) and Talus. The Reef Reservoir has the most potential content of gaseous hydrocarbons, while Talus has the potential to increase the number of reserves in the OGIP calculations in the MIM field, which were not previously identified and not taken into account in previous studies. Based on the results of three-dimensional reservoir modeling and OGIP calculations, it shows that the reef tip layer has an average OGIP value that is greater than the OGIP calculation in the previous study, namely 118.5 BSCF. While the results of this study obtained an OGIP value of 176.5 BSCF. Furthermore, the Talus layer in the previous study was not considered in the OGIP reserve figure, in this study the Talus obtained an OGIP value of 110.9 BSCF. The results of the distribution analysis and three-dimensional modeling produced by the Kujung reef and Talus layers have a significant effect on volumetric calculations, namely increasing the estimated OOIP of oil by 58 MMBO and the OGIP value of gaseous hydrocarbons by 110.9 BSCF.